Author Correction: Homogeneity evaluation of mesenchymal stem cells based on electrotaxis analysis. Issue 1 (December 2018) - Kim, Min; Lee, Mi; Kwon, Byeong-Ju; Kim, Dohyun; Koo, Min-Ah; Seon, Gyeung; Park, Jong-Chul
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper.